Business Accelerators for Climate Change Adaptation in East and Southern Africa: The value of tailor-made and co-designed approaches for Food Systems Transformation - Lozano, Denise; Dam Lam, Rodolfo; Zulu, Mercy; Rossignoli, Cristiano (WorldFish, 2024)
Business accelerators play a central role in the dissemination and scaling of innovations across food systems, brought about by high performing small and medium enterprises. This role is even more critical in nascent entrepreneurial ecosystems and value chains.